Pengalaman literasi informasi anggota lembaga pers mahasiswa dalam produksi karya jurnalistik - Sulistiyani, Rizka Sulistiyani; Heriyanto, Heriyanto (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2025)
Purpose. The purpose of this study is to explain the information literacy experiences of LPM Hayamwuruk members in compiling journalistic works Methodology. his study utilizes a qualitative research methodology, specifically a phenomenology approach, to explore and understand the experiences, meanings, and perceptions of the research participants. Results and discussion. The research obtained a comprehensive understanding of the experience information literacy of LPM Hayamwuruk members who demonstrated a critical approach to information. They effectively utilized their information literacy skills, which enable them to execute journalistic activities with proficiency Conclusions. Those themes present how broad their world of information literacy in journalism is, especially regarding the sources of information used to obtain data and information, how the information they obtain is arranged into news, forming arguments in expressing opinions, and assessing a literary work.